Globalization and entrepreneurship in small countries - Marković, Mirjana Radović, author.
1 online resource.
Keywords: The changeable business environment requires a new business framework and an understanding of the global market trends and the culture that will impact on business. Globalization and Entrepreneurship in Small Countries considers important business principles and makes them accessible for entrepreneurs and small business owners. It addresses the role of managers and leaders and management techniques in the context of global strategy of companies, as well as the culture diversity that comes with globalization of organizations. To meet the constantly changing conditions and demands, business must transcend boundaries to get what it needs regardless of where it exists - geographically, organizationally, and functionally. This book draws together earlier literature on SME development and internationalization from disparate sources into a cohesive body of work, which traces the evolution of our understanding of the topic. It explores just how globalization affects the demand for business and entrepreneurship, and will therefore be of interest to researchers, academics, policymakers, and students in the fields of entrepreneurship, globalisation, organisational studies, and SMEs development in small countries.